Factors Associated With Child Maltreatment Among Children Aged 11 to 17 Years in Community Settings of Karachi, Pakistan, Using Belsky Ecological Framework - Lakhdir, Maryam Pyar Ali (Journal of interpersonal violence, 2021)
Child maltreatment is considered as a global social issue and results as combined effect of parental background, socioeconomic environment, family structure, and child characteristics. The aim of this study was to determine factors associated with child maltreatment among children aged 11 to 17 years in Karachi, Pakistan. A cross-sectional survey of 800 pairs (children ranging from 11 to 17 years old and their parents) was randomly selected from 32 clusters of Karachi, using multistage cluster sampling. A structured questionnaire was adopted from the International Society for the Prevention of Child Abuse and Neglect (International Child Abuse Screening Tool for Parent [ICAST-P] and for Child [ICAST-C]). Multiple linear regression technique was used to assess the association of factors with child maltreatment score, by using STATA software. Our study found that children who always get bullied and mistreated by their siblings are at increased risk of getting maltreatment by parents (adjusted β: 10.78, 95% CI = [8.5, 13.05]).The mean estimated ICAST-C score increases by 9.86 (95% CI = [6.17, 13.55]) for children with exposure of verbal abuse and quarrel within family members. The mean estimated ICAST-C score increases by 5.09 among male children as compared with female children (95% CI = [3.65, 6.52]). Among children whose family always fight with each other and whose parents have exposure to childhood maltreatment, the mean estimated ICAST-C score increases by 22.25 (95% CI = [16.53, 27.98]). This study reflects the potential factors of child maltreatment in Karachi. Our findings provide evidence to raise awareness about child maltreatment.